Gene loss, co-option and the evolution of developmental complexity in the volvocine algae - Jimenez Marin, Leticia Berenice (Kansas State University, 2023)
The evolution of multicellularity is a Major Evolutionary Transition that has occurred in each domain of life and has evolved independently numerous times in diverse eukaryotic lineages. Multicellularity is associated with changes to developmental complexity; this is thought to be a consequence of multicellular species collectively organizing into higher level individuals. Hence, extant descendants of early multicellular lifeforms exhibit a wealth of morphological and developmental innovations. Despite the recurring nature and biological importance of multicellular evolution, determining the molecular mechanisms underlying it presents several challenges. Most notably, in most multicellular lineages there are long divergence times between multicellular species and their unicellular relatives that obscures the genetic signature of multicellular evolution. Moreover, most systems used to study the evolution of multicellularity lack important experimental toolkits to dissect the molecular basis of multicellular evolution. However, the volvocine algae have several advantages to the study the molecular bases of the transition to multicellularity and developmental complexity. Extant volvocine species exhibit a stepwise increase in multicellular and developmental complexity; member species have phenotypes ranging from unicellular, to undifferentiated multicellular, and to differentiated multicellular. This group evolved multicellularity relatively recently (~250 MYA) resulting in a high degree of genomic similarity and conserved synteny that suggests few genetic changes are required for lineages to undergo dramatic shifts in multicellular and developmental complexity. Multicellularity in the volvocines is thought to have evolved by co-option of key genes, such as cell cycle and developmental regulators. However, these co-opted genes appear to be an exception rather than a rule underlying developmental features observed in multicellular volvocine species (Chapter 1). In this work, comparative genomics (Chapters 2 and 3), mathematical modeling (Chapter 2), molecular biology (Chapters 2 and 5), comparative transcriptomics (Chapter 4), and reverse genetics (Chapter 5) approaches are used to provide an integrative view on how gene loss and co-option have impacted the volvocine transition to multicellularity and increased developmental complexity, with implications for other systems. Results show that genetic co-option of fsl1 impacted the evolution of cell-cell adhesion – a key aspect of multicellular life, in undifferentiated multicellular Gonium pectorale. Furthermore, a putative environmental response gene, rlsD, has overlapping targets with its paralog, a cell differentiation regulator in Volvox carteri. Importantly, further results demonstrate that significant loss of conserved genes occurred in the volvocine lineage. These bursts of gene loss likely occurred after the divergence between the lineage of unicellular Chlamydomonas and the ancestor of multicellular volvocines, potentially setting the stage for multicellularity to evolve. Moreover, gene losses are shared across two volvocine families that independently evolved cell differentiation programs, further suggesting that gene loss might have facilitated the evolution of complex phenotypes across the volvocine lineage. Gene loss events likely impact the evolutionary paths and constraints of other genes, potentially resulting in molecular network rewiring and stabilization of the multicellular state. As means to expand these findings to other systems, a mathematical model is developed that suggests the evolution of many multicellular traits might be the product of gene-regulatory and functional innovations that do not necessarily require expansion of genetic repertoires.
Keywords: Multicellularity, Volvocine algae, Genomics, Transcriptomics